2016
DOI: 10.1007/s11274-016-2107-3
|View full text |Cite
|
Sign up to set email alerts
|

Secretome, surfome and immunome: emerging approaches for the discovery of new vaccine candidates against bacterial infections

Abstract: Functional genomics has made possible advanced structure-to-function investigation of pathogens and helped characterize virulence mechanisms. Proteomics has been become a tool for large-scale identification of proteins involved during invasion and infection by the pathogens. Bacterial surface and secreted proteins play key role in the interaction between the bacterial cell and the host environment. Thus exoproteome and surface proteome of a microorganism are hypothesized to contain components of effective vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…In addition, GGT was classified as a periplasmic protein, as shown in Table 1. Surface and extracellular proteins are good targets to develop a vaccine aiming toward prevention of bacterial infections and diseases (Dwivedi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, GGT was classified as a periplasmic protein, as shown in Table 1. Surface and extracellular proteins are good targets to develop a vaccine aiming toward prevention of bacterial infections and diseases (Dwivedi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics is an important tool to identify potential vaccine antigens, and is especially useful for pathogens such as S. aureus that express numerous surface exposed proteins (Collado et al, 2016; Dwivedi et al, 2016). Studies have reported the use of 2-dimensional electrophoresis ( 2DE ) for whole or subcellular proteome analysis of Staphylococcus for human vaccine development (Sellman et al, 2005; Brady et al, 2006; Solis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristics of a good vaccine is to possess a surface charge with isoelectric point and molecular weight less than 50,000 kDa that is why Pi/Mw server was used to calculate the isoelectric point and molecular weight to get the surface charge of the proteins as it is essential for the vaccine. Another features of a good vaccine candidate is possession of good antigenic properties, which are crucial for the pathogenesis of the organism and for protection against its infectivity [34,35]. Some earlier studies have implored these approaches in the selection of candidate proteins for the in silico design of probable E.coli vaccine candidates as reported here [36][37][38].…”
Section: Discussionmentioning
confidence: 99%